PEMBERDAYAAN KELOMPOK PETERNAK ITIK KABUPATEN SRAGEN MELALUI PRODUKSI KONSENTRAT ITIK SECARA MANDIRI SEBAGAI UPAYA SUSTAINABLE USAHA PEMELIHARAAN DAN PENGURANGAN KETERGANTUNGAN TERHADAP PRODUSEN PABRIK PAKAN - Dewanti, Ratih; Sudiyono, Sudiyono; Rahayu, Endang Tri (LPPM UNS, 2016)
IBM's activities implemented in Nusupan Wetan, Celep, Kedawung, Sragen with partners â€œRejeki Agungâ€ Ducks Farmer Group Suhardi and KTI Mandiri. The purpose of activities is to improve the income and welfare of farmers through the ability of farmers in the manufacture of concentrate ducks reducing dependency fromFeedmill.The problems is high price of duck concentrates, has not mastered the preparation of feed,not support equipment manufacture concentrate and lack of knowledge of managerial and bookkeeping. The method used is counseling, mentoring, training, making concentrate, pellet , maintenance practices ducks and mentoring activities. In this activity given mixer machine, pellet machine, oven, concentrate packaging sacks, bamboo cages and feed materials making up the duck concentrate.Results showed dedication that these activities can increase ability and skill of group farmers and productivity of duck concentrate. The day could produce 2000 kg / 10 hours with savings of not buying the concentrate from feedmill Rp.4.460.000/day. Introductions mixer and pellet machines run well. Equipment can be applied properly.Keywords: Animal group Ducks, Concentrate, Sragen